Effect of dynamic seeding methods on the distribution of fibroblasts within human acellular dermis - Vitacolonna, Mario; Belharazem, Djeda; Hohenberger, Peter; Rößner, Eric (Cell and tissue banking, 2015)
The purpose of this investigation was to compare different dynamic cell seeding methods regarding their seeding efficiency, homogeneity, infiltration depth and proliferation within a human acellular dermis. In addition, the growth behaviour was observed during a 12-day static in vitro culture. The dynamic methods included orbital-shaker seeding and the use of a plate centrifuge with different rotational speeds, combinations of low-pressure for matrix degassing and centrifugal seeding. Scaffolds were incubated for up to 12 days statically. Cell distribution and infiltration depth were analysed histologically at days 0, 4, 8 and 12. Seeding efficiency and cell proliferation were quantified with the MTT-assay at the same time points. Centrifugal seeding with 300g for 5 × 1 min combined with matrix degassing significantly increased the seeding efficiency and homogeneity compared to the other methods. However, following static culture, no cells were detectable after 4 days in the inner matrix zones. Furthermore, none of the degassing+centrifugation groups reached a significantly higher proliferation at day 8 compared to the reference. The use of a single dynamic method resulted in an inefficient cell seeding. We archived the highest seeding efficiency, homogeneity and infiltration depth using a combination of degassing+centrifugation at 300g for 5 × 1 min.
Gesehen am 06.12.2018